Synergistic luminescent thermometer using co-doped Ca2GdSbO6:Mn4+/(Eu3+ or Sm3+) phosphors. Issue 12 (28th February 2022) - Li, Guixian; Xue, Yu; Mao, Qinan; Pei, Lang; He, Hong; Liu, Meijiao; Chu, Liang; Zhong, Jiasong
Abstract : The high temperature sensitivity of Ca2 GdSbO6 :Mn 4+ /(Eu 3+ or Sm 3+ ) phosphor has been used for constructing a luminescence thermometer. Abstract : Luminescent thermometers provide a non-contact method of probing temperature with high sensitivity and response speed at the nanoscale. Synergistic photoluminescence from different activators can realize high sensitivity for luminescent thermometers by finely selecting ions with specific crystallographic sites. Herein, the more temperature-sensitive Mn 4+ and the less-sensitive Eu 3+ (or Sm 3+ ) activators are co-doped into a Ca2 GdSbO6 matrix to form an effective thermometer, where Mn 4+ and Eu 3+ (or Sm 3+ ) ions occupy the Sb 5+ and Gd 3+ sites, respectively. The co-doping of Eu 3+ ions or Sm 3+ ions leads to lattice expansion of Ca2 GdSbO6 matrix and a tuned narrow emission from deep-red to orangish-red. According to the ratio of luminescence intensity, the maximal S a and S r values are 0.19 K −0 (347 K) and 1.38% K −( (420 K) for Ca2 GdSbO6 :Mn 4+ /Eu 3+ probe and 0.26 K −p (363 K) and 1.55% K −( (430 K) for Ca2 GdSbO6 :Mn 4+ /Sm 3+ probe thermometers, respectively. In addition, thermometers based on Mn 4+ emission lifetimes can provide the highest relative sensitivity of 1.47% K −s at 425 K. Thus, the highly-temperature-sensitive Ca2 GdSbO6 :Mn 4+ /(Eu 3+ or Sm 3+ ) phosphor is a promising candidate for practical luminescence thermometers.